2013
DOI: 10.1126/science.1239451
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Dirac Node Formation and Mass Acquisition in a Topological Crystalline Insulator

Abstract: In topological crystalline insulators (TCIs), topology and crystal symmetry intertwine to create surface states with distinct characteristics. The breaking of crystal symmetry in TCIs is predicted to impart mass to the massless Dirac fermions. Here, we report high-resolution scanning tunneling microscopy studies of a TCI, Pb(1-x)Sn(x)Se that reveal the coexistence of zero-mass Dirac fermions protected by crystal symmetry with massive Dirac fermions consistent with crystal symmetry breaking. In addition, we sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
284
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 290 publications
(300 citation statements)
references
References 25 publications
(37 reference statements)
16
284
0
Order By: Relevance
“…This prediction was later verified by the direct observation of topological surface states in the ARPES experiments [7][8][9]. Signatures of surface states have also been observed in transport and scanning tunneling microscopy (STM) measurements [10][11][12]. Remarkably, a recent STM experiment on (001) surface states in a magnetic field by Okada et al [11] has found interesting features in the Landau levels that are not expected for a pristine TCI surface but are consistent with a particular type of mirror symmetry breaking due to structural distortion [5].…”
Section: Introductionmentioning
confidence: 53%
“…This prediction was later verified by the direct observation of topological surface states in the ARPES experiments [7][8][9]. Signatures of surface states have also been observed in transport and scanning tunneling microscopy (STM) measurements [10][11][12]. Remarkably, a recent STM experiment on (001) surface states in a magnetic field by Okada et al [11] has found interesting features in the Landau levels that are not expected for a pristine TCI surface but are consistent with a particular type of mirror symmetry breaking due to structural distortion [5].…”
Section: Introductionmentioning
confidence: 53%
“…A topological crystalline insulator (TCI) is a new symmetry protected topological phase that is protected by crystalline space group symmetries [16][17][18] . The surface states of this novel topological phase are predicted to host many uniquely-new quantum phenomena, including surface spin filtering 19 , strain-induced crystalline symmetry protected Chern currents 20 , correlation physics due to surface electronic singularities 21,22 , none of which are possible in the much studied Z 2 TI 1,2 . The realization of these proposals requires the ability to control a TCI material to be topological or non-topological as a function of various material parameters, and to understand the properties of the protected surface states under all these parameter conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Pairs of Dirac cones with spin-momentum locking are located near theX points of the surface Brillouin zone, forming a Kramers pair. At low temperatures the surface undergoes a structural transition into a ferroelectric state and one of the mirror symmetries is spontaneously broken [14,15], while the other remains intact. As a result, two of the surface Dirac cones become massive, while the other two remain massless [16] (see inset in Fig.…”
mentioning
confidence: 99%